Deep brain stimulation targeting in refractory epilepsy. (April 2017) - Cukiert, Arthur; Lehtimäki, Kai
Summary: Deep brain stimulation has been used in increasing frequency to treat refractory epilepsy. Different targets have been tried, and different epileptic syndromes have been addressed in different ways. We describe the current targeting techniques for the structures presently most often implanted, namely the anterior nucleus of the thalamus, the centromedian nucleus of the thalamus, and the hippocampus.